2008
DOI: 10.1103/physrevb.77.172404
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of the quantum Ising model in the two-dimensional kagome lattice

Abstract: In the classical Ising model on the kagome lattice, there are macroscopically degenerate classical states with exponentially-decayed spin correlation. As the singular quantum perturbation is introduced by applying the transverse magnetic field, the quantum ground state remains disordered, dubbed by "disorder-by-disorder". Here we compute the temperature dependence of the spin susceptibility and the specific heat for difference strength of the field to understand the effect of the singular quantum perturbation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…For K = 0.01, the susceptibility in the low temperature is too small beyond the precision of the machine. Similar to the antiferromagnetic quantum Ising model in the kagome lattice 14 , the smooth transformation of the magnetic susceptibility in the variation of K is consistent with the analysis in Ref. [11].…”
Section: B Magnetic Susceptibilitysupporting
confidence: 88%
“…For K = 0.01, the susceptibility in the low temperature is too small beyond the precision of the machine. Similar to the antiferromagnetic quantum Ising model in the kagome lattice 14 , the smooth transformation of the magnetic susceptibility in the variation of K is consistent with the analysis in Ref. [11].…”
Section: B Magnetic Susceptibilitysupporting
confidence: 88%
“…It illustrates the double-peak structure and the reason is similar to the one given in the Ref. [11]. Although the valley between the peaks is not as deep as the experimental one shown in Ref.…”
supporting
confidence: 84%
“…This system has a highly degenerate ground state [2] and any small perturbation to the Hamiltonian can severely affect the ground state manifold. The perturbations can be: exchange anisotropy [3], bond anisotropy [4,5], transverse field [6,7], Dzyaloshinksy-Moriya Interaction (DMI) [8,9,10], or longer range interactions [11]. Therefore, numerous theoretical directions have been taken to predict the low-temperature behavior of the kagomé system, and some of them were particularly applied to magnetization and other measurements of the herbertsmithite [10][12].…”
mentioning
confidence: 99%
“…1: (Color online) X-ray diffraction of powder (black) and oriented powder (gray) from a surface perpendicular to the orienting field. [10,19] or anisotropy in the bonds [4,7]. It was also suggested that impurities from a Zn/Cu substitution play a significant role in the low-temperature susceptibility [17][20, 21].…”
mentioning
confidence: 99%